A 12-year-old boy presenting with unilateral proximal interphalangeal joint swelling. (13th April 2011) - Small, S; Murthy, V; Sridhar, A V
Abstract : Pachydermodactyly is a rare and benign superficial dermal fibromatosis, characterised by asymptomatic soft tissue hypertrophy of the lateral and dorsal aspects of the proximal interphalangeal joints. The majority affected are males, with only a few reported female cases, and usually begins to develop around the age of puberty. Pachydermodactyly affects the second, middle and ring fingers of the hand symmetrically and bilaterally. The majority of reported cases demonstrate bilateral involvement of joints, only a small proportion report unilateral involvement. In this case report the authors review literature and discuss a case of pachydermodactyly presenting a unilateral swelling of the proximal interphalangeal joints of only the left hand in a right-handed young male.